Analysis of Financial Stability Determinants in Indonesia - Antonius W Nugroho; Mohamad Adam; Marlina Widiyanti; Sulastri Sulastri (Syntax Corporation Indonesia, 2021)
Financial Stress Index (FSI) is one of the indices to measure financial stress which can lead to a financial crisis. Quantitative analysis was conducted to some banking sector performance indicator which impacts financial stability with FSI as a proxy. Data population was taken from banking company listed in Indonesian Stock Exchange, sampling using purposive sampling of 38 banks. Using pooled data regression analysis was founded that NPL, CAR, and ROA positively significant to financial stability, while NIM negative but not significant to financial stability. The research found that NPL and NIM are not in line with the hypothesis. NPL is an indicator for bad debt, which means that increase in NPL will make financial stability vulnerable, but the research shows that an increase in NPL causes financial stability incline to increased, this could have happened if any other factors maintain financial stability tend to increase. On the other hand, NIM is decreasing which means the productivity of banks decreased but financial stability tends to increase because other factors that maintain financial stability tend to increase.